2011
DOI: 10.1080/14789949.2010.518244
|View full text |Cite
|
Sign up to set email alerts
|

Familicide and suicide in a case of gambling dependence

Abstract: A former army officer unexpectedly killed his wife and two daughters by strangulation and afterwards hanged himself. Psychological autopsy (police investigation, forensic expertise, psychiatric records and interviews) showed how an ordinary young man, functioning well at work and normally in family life, had become a homicide-suicide perpetrator. The study brings out the complex of risk factors for suicidal crisis: violent and risk-taking behaviour, impulsivity, depression, attempted suicide, pathological gamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…However, a recently emerging body of literature includes psychiatric studies linking shame and suicide (Wiklander et al 2012;Bryan et al 2013;Anderson, Sisask, and Varnik 2011;You et al 2012), a qualitative investigation of patients who had attempted suicide that included evidence of feelings of shame (Vatne and Nåden 2012) and studies that demonstrate that the experience of shame is implicated in queer youth suicide (Cover 2012;McDermott, Roen, and Scourfield 2008). This body of literature constitutes a framework that renders shame visible in relation to suicide.…”
Section: The Cultural Politics Of Shame and Suicidementioning
confidence: 97%
“…However, a recently emerging body of literature includes psychiatric studies linking shame and suicide (Wiklander et al 2012;Bryan et al 2013;Anderson, Sisask, and Varnik 2011;You et al 2012), a qualitative investigation of patients who had attempted suicide that included evidence of feelings of shame (Vatne and Nåden 2012) and studies that demonstrate that the experience of shame is implicated in queer youth suicide (Cover 2012;McDermott, Roen, and Scourfield 2008). This body of literature constitutes a framework that renders shame visible in relation to suicide.…”
Section: The Cultural Politics Of Shame and Suicidementioning
confidence: 97%
“…It was observed that pathological gambling increased the odds of perpetrating dating violence, severe marital violence, and severe child abuse even when adjusted for mental disorders [125]. Pathological gambling has also been observed to be associated with homicide in the family [105, 126]. Additionally, among problem gamblers, 63% had been victims or perpetrated intimate partner violence (IPV) [127].…”
Section: Main Textmentioning
confidence: 99%
“…The murder of a child ( filicide ), without murdering the spouse or the perpetrator committing suicide, is also considered one form of familicide [59]. Other terms used to refer to the concept of familicide include familicide-suicide, filicide-suicide and extended suicide where the perpetrator also commits suicide [10,11]. In this literature review, familicide is used to refer to the killing of the child or the whole family with at least one family member killed by another adult family member.…”
Section: Introductionmentioning
confidence: 99%